THE USE OF LOCAL HERBAL IN ALTERNATIVE AND COMPLEMENTARY THERAPIES AS MIDWIFERY CARE SYNERGISTIC THERAPY IN SASAK ETHNIC - Triandini, I Gusti Agung Ayu Hari; Hairani, Hairani (Jurnal Silva Samalas, 2024)
Traditional healers are still the main choice of the Sasak tribe to assist with childbirth. The city of Mataram ranks second lowest in terms of the percentage of births assisted by health workers and the third lowest in the West Nusa Tenggara region in terms of the percentage of births in health service facilities because of holistic service experience, culture, education, and outreach to health facilities factors. Traditional health services have been proven for a long time and are used by the community in preventive, promotive, curative, and rehabilitative efforts. This is very useful, especially in areas where access to health services is limited. The term "integrative medicine" in synergistic therapy is used to refer to the combination of conventional and alternative medicine practices that meet the requirements of scientific evidence, safety, and effectiveness. A descriptive, cross-sectional, quantitative method was used to assess 30 traditional healers in the Mataram city area. The complementary therapies in midwifery care help to reduce symptoms such as nausea vomiting and lower back pain, prepare for labor and increase the chances of an uncomplicated birth, increase milk production or reduce pain in perineum wounds, and also to accelerate the recovery of postpartum maternal health conditions using traditional herbal therapy such as pilis, parem, tapel, serbat, boreh. It has many benefits and needs to be introduced to midwives to be more optimal in providing holistic midwifery services.